Միջնադարյան Թուրքիայի պատմության կեղծարարությունները քեմալական պատմագրության մեջ - Ա. Ս. Տվերիտինովա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
The medieval history of Turkey was subject of different scientific debates, especially after the restitution of Turkish government having as its head Mustafa Kemal Ataturk.
Keywords: History